FORMULATION AND CHARACTERIZATION EFFERVESCENT TABLETS OF GAMBIER LEAF EXTRACT (Uncaria gambier Roxb) - Putu Rismayanti Putri; I Gusti Ngurah Agung Windra Wartana Putra; Ni Putu Wintariani; Ni Putu Aryati Suryaningsih (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2024)
Background: Gambier, also known as the term (Uncaria gambier Roxb), is a plant that has long been cultivated in Indonesia. The components of flavonoid compounds in gambier plants have been widely reported as antioxidants. Using the gambier plant will be more accessible and more practical if it is made in dosage form, one of which is in the form of effervescent tablets. Objective: To determine the physical and chemical characteristics of effervescent tablets of gambier leaf extract (Uncaria gambier Roxb). Methods: Descriptive design, which includes phytochemical screening research, extract quality test, physical and chemical characteristics test of effervescent tablets formulation. Results: Positive gambier leaf extracts contain flavonoid compounds, alkaloids, tannins, and saponins. The average weight uniformity test of the tablet is 1.57 ± 0.02 grams, the average tablet thickness test of the tablet is 0.5±0 cm while a tablet's average diameter is 1.6±0 cm, the fragility test obtained <1%, the average hardness test of the tablet is 4.34±0.02 kg, the solubility time of the tablet obtaining is 1.6 ±0.4 minutes and tablets pH is 5.5±0.2. Conclusion: It is possible to draw the conclusion that the positive gambier leaf extract includes flavonoid components, alkaloids, tannins, and saponins based on the findings of the data previously gathered. The quality test of gambier leaf extract is already qualified, and the test of the characteristics of the physical and chemical properties produced is suitable based on Pharmacopeia Indonesia Standard. Keywords: Gambier; Extract; Tablet Effervescent